2015
DOI: 10.1002/iid3.43
|View full text |Cite
|
Sign up to set email alerts
|

Direct Toll‐Like Receptor 8 signaling increases the functional avidity of human CD8+ T lymphocytes generated for adoptive T cell therapy strategies

Abstract: Adoptive transfer of in vitro activated and expanded antigen-specific cytotoxic T lymphocytes (CTLs) is a promising therapeutic strategy for infectious diseases and cancers. Obtaining in vitro a sufficient amount of highly specific cytotoxic cells and capable of retaining cytotoxic activity in vivo remains problematic. We studied the role of Toll-Like Receptor-8 (TLR8) engagement on peripheral CTLs activated with melanoma antigen MART-1-expressing artificial antigen-presenting cells (AAPCs). After a 3-week co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The functional avidity is one of the crucial determinants of T cell functionality. Although the process of primary T cells regulates their sensitivity to peptide antigen in vitro is disclosed 19 20 21 22 , how VACV tunes the low avidity CD8 + T cells induced by DNA vaccination into high avidity ones in vivo is still not defined. Previously, we had proved that the improved functional avidity of T cells induced by VACV is mediated by intrinsic MyD88 mediated signaling pathways in CD8 + T cells, instead of antigen presentation efficacy, TCR affinity, or the VACV infection induced MyD88-mediated inflammatory milieu 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional avidity is one of the crucial determinants of T cell functionality. Although the process of primary T cells regulates their sensitivity to peptide antigen in vitro is disclosed 19 20 21 22 , how VACV tunes the low avidity CD8 + T cells induced by DNA vaccination into high avidity ones in vivo is still not defined. Previously, we had proved that the improved functional avidity of T cells induced by VACV is mediated by intrinsic MyD88 mediated signaling pathways in CD8 + T cells, instead of antigen presentation efficacy, TCR affinity, or the VACV infection induced MyD88-mediated inflammatory milieu 27 .…”
Section: Discussionmentioning
confidence: 99%
“…It’s well shown that an individual T cell clone can be generated into both high- and low-avidity effectors by in vitro stimulation with a high or low concentration of peptide, respectively, which is determined by the initiation of T cell receptor (TCR) signaling 19 20 21 . Moreover, the Toll-like receptor 8 engagement increased anti-tumor cytotoxic T lymphocyte (CTL) functional avidity in vitro 22 . Currently, it’s well demonstrated that T cells could undergo a process called functional avidity maturation when encountered with the antigen, leading to the increased avidity in antigen experienced cells compared to naïve ones 23 .…”
mentioning
confidence: 99%
“…SelgantolimodNucleotide analogue[44,45] TLR7/TLR8Resiquimod Imidazoquinoline compound derivative[24,38,40] CL075Thiazoloquinolone derivative[29,[46][47][48] …”
mentioning
confidence: 99%
“…Acting on different transcriptional repression mechanisms is most likely key factor for efficient reversion of HIV latency (75,76). We tested the hypothesis that prostratin (acting directly on latently infected T cells), in concert with TLR8ag (acting via DCs), disrupts HIV latency (67) and might trigger the priming and restoration of antigen-specific immunity, through costimulatory molecules and IL-12p70 expression (71,77,78). Adding TLR8ag might lead to a Th1 supportive milieu crucial to clear the persistent quiescent reservoir in vivo.…”
mentioning
confidence: 99%